The Challenge of Maintaining a Healthy Microbiome during Long-Duration Space Missions - Voorhies, Alexander A.; Lorenzi, Hernan A. (Frontiers in Astronomy and Space Sciences, 2016)
Astronauts will face a host of challenges on long-duration space missions like a human expedition to Mars, including the difficulty of maintaining a balanced and healthy microbiome. The human microbiome is the collection of all microorganisms residing in and on a human host, and it plays an essential role in keeping humans healthy. However, imbalances in the microbiome have also been linked to many human diseases. Space travel has been shown to alter the microbiome of astronauts in ways that are not yet completely understood. Here we review past and current microbiology and microbiome research with the aim of determining the extent of change to the human microbiome caused by space travel and implications for astronaut health. We also address several challenges that will need to be overcome in order to facilitate long-duration human exploration missions. These challenges include maintaining environmental conditions that favor healthy microbiomes, controlling the microbial organisms astronauts are exposed to, the impact of galactic cosmic radiation on the microbiome, and medical interventions that can potentially damage the microbiome.